Determination of User Satisfaction of Seafarer's Book Service: Analysis of Service Quality, Facilities, and Standard Operating Procedures at KSOP Class II Marunda - Honny Fiva Akira Sembiring; Asep Suparman; Fransisca Pratiwi; Reza Jaya Sakti; Chandra Mardika Saputra (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Determination of Seafarer's Book Service User Satisfaction: Analysis of Service Quality, Facilities, and Standards Operating Procedure at Ksop Class II Marunda is a scientific literature review article. The purpose of this article is to develop a hypothesis of the influence of variables that will be used in further research. The objects of this research are online libraries, Google Scholar, Mendeley, and other academic online media. The research method uses library research sourced from e-books and open-access e-journals. The results of this article are: 1) the effect of service quality on service user satisfaction; 2) the effect of facilities on service user satisfaction; 3) the effect of SOP on service user satisfaction.